Clinical impact of amotosalen‐ultraviolet A pathogen‐inactivated platelets stored for up to 7 days. Issue 11 (1st October 2019) - Infanti, Laura; Holbro, Andreas; Passweg, Jakob; Bolliger, Daniel; Tsakiris, Dimitrios A.; Merki, Ramona; Plattner, Alexandra; Tappe, David; Irsch, Johannes; Lin, Jin‐Sying; Corash, Laurence; Benjamin, Richard J.; et al.
Abstract : BACKGROUND: Universal pathogen inactivation of platelet concentrates (PCs) using amotosalen/ultraviolet A with 7‐day storage was implemented in Switzerland in 2011. Routine‐use data were analyzed at the University Hospital Basel, Switzerland. STUDY DESIGN: A retrospective two‐cohort study of patient and PC characteristics, component usage, patient outcomes, count increments (CIs), and adverse events were analyzed for two consecutive 5‐year periods with either 0‐ to 5‐day‐old conventional PC (C‐PC) (n = 14, 181) or 0‐ to 7‐day‐old pathogen‐inactivated PC (PI‐PC) (n = 22, 579). RESULTS: In both periods, PCs were issued for transfusion on a "first in, first out" basis. With 7‐day PI‐PC, wastage was reduced from 8.7% to 1.5%; 16.6% of transfused PI‐PCs were more than 5 days old. Transfusion of PI‐PC more than 5 days old compared with 5 days old or less did not increase platelet and RBC use on the same or next day as an indirect measure of hemostasis and did not increase transfusion reactions. Mean corrected count increments (CCIs) for PI‐PC stored for 5 days or less were 22.6% lower than for C‐PC (p < 0.001), and declined with increasing storage duration for both, although the correlation was weak (r 2 = 0.005‐0.014). Mean number of PCs used per patient and duration of PC support were not different for hematology/oncology, allogeneic and autologous hematopoietic stem cell transplant (HSCT), and general medical/surgical patients, who used the majority ( 92.0%) of PI‐PCs. Five‐year treatment‐related mortality in allogeneic HSCT was unchanged in the PI‐PC period. CONCLUSIONS: PI‐PCs with 7‐day storage reduced wastage and did not increase PC or red blood cell utilization or adverse reactions compared with fresh PI‐PC or a historical control group, demonstrating preserved efficacy and safety.